2010
DOI: 10.1007/s13313-010-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ‘alternative’ materials to sulfur and synthetic fungicides for control of grapevine powdery mildew in a warm climate region of Australia

Abstract: The efficacy of 'alternative' materials against powdery mildew (Erysiphe necator)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Treatments containing whole milk powder and whey proteins gave variable disease control depending on the concentration (g/L) of the active ingredient, purity of the product, and the nature of co-ingredients, and were associated with sooty mould growth in the presence of heavy whitefly populations. Savocchia et al (2011) also observed that PM disease control efficacy of whole milk and whey protein was inconsistent and diminished over the course of two seasons' trial work on field-grown grapes. They concluded that these products were most suited to use on grape cultivars that were less susceptible to PM such as 'Cabernet Sauvignon' and 'Shiraz' and was best suited to conditions of low disease pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments containing whole milk powder and whey proteins gave variable disease control depending on the concentration (g/L) of the active ingredient, purity of the product, and the nature of co-ingredients, and were associated with sooty mould growth in the presence of heavy whitefly populations. Savocchia et al (2011) also observed that PM disease control efficacy of whole milk and whey protein was inconsistent and diminished over the course of two seasons' trial work on field-grown grapes. They concluded that these products were most suited to use on grape cultivars that were less susceptible to PM such as 'Cabernet Sauvignon' and 'Shiraz' and was best suited to conditions of low disease pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Milk products have been used informally as bio-fungicides for many years with varying success (Bettiol 1999;Ferrandino & Smith 2007;Savocchia et al 2011;Martins et al 2016), but have not been commercialised, due to problems such as milk spoilage, handling difficulties, poor durability of control, and unwanted growth of non-target organisms. Milk is a nutritionally complex mixture and some of its components have antimicrobial activity, such as whey protein (Crisp et al 2006;Bettiol et al 2008) and fats (Horincar & Bahrim 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This study represents the first report of AMF being used to control powdery mildew, and the first report of the use of SBO against apple PM since 1993 (Northover & Schneider 1993). Savocchia et al (2011) evaluated milk and botanical oils for control of grapevine powdery mildew, but data from three seasons showed that these products provided relatively poor disease control on Chardonnay grapes. Although SBO has been used in trials to control PM in other crops, results have been variable (Northover & Schneider 1996;Jee et al 2009), probably because of differences in formulation.…”
Section: Figurementioning
confidence: 95%
“…Such diversified approaches to powdery mildew management may reduce the risk of causal organisms developing resistance to some fungicides (Erickson and Wilcox, 1997). Elemental sulfur is also commonly used to control powdery mildew in organic production systems because it works relatively well under low inoculum conditions early in the season and will help to reduce applications of more effective but more resistance-prone material later in the season during peak disease infection (Savocchia et al, 2011;Smith et al, 2014). When applied to tolerant vines, sulfur is a relatively inexpensive and effective complement to other fungicides for effective control and prevention of resistance (Bordelon et al, 2016).…”
mentioning
confidence: 99%